The NFL true fan problem - Whittle, Scott (Kansas State University, 2014)
Throughout an NFL season, 512 games are played in 17 weeks. For a given fan that follows one team, only 16 of those games usually matter, and the rest of the games carry little significance. The goal of this research is to provide substantial reasons for fans to watch other games. This research finds the easiest path to a division championship for each team. This easiest path requires winning the least number of games. Due to NFL’s complicated tiebreaker rules, games not involving the fan’s team can have major implications for that team. The research calls these games critical because if the wrong team wins, then the fan’s team must win additional games to become the division champion. To identify both the easiest path and the critical games, integer programming is used. Given the amount of two-team, three-team, and four-team division tie scenarios that can occur, 31 separate integer programs are solved for each team to identify the easiest path to the division championship. A new algorithm, Shortest Path of Remaining Teams (SPORT) is used to iteratively search through every game of the upcoming week to determine critical games. These integer programs and the SPORT algorithm were used with the data from the previous 2 NFL seasons. Throughout these 2 seasons, it was found that the earliest a team was eliminated from the possibility of winning a division championship was week 12, and occurred in 2012 and 2013. Also, throughout these 2 seasons, there was an average of 65 critical games per season, with more critical games occurring in the 2013-2014 season. Additionally, the 2012 season was used to compare flexed scheduled games with the critical games for those weeks and it was found that the NFL missed three weeks of potentially scheduling a critical game.
Keywords: Operations Research; Integer Programming; National Football League; Industrial engineering; Industrial Engineering (0546); Operations Research (0796)